2018
DOI: 10.1002/phar.2108
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness Analysis of Sacubitril/Valsartan for the Treatment of Heart Failure with Reduced Ejection Fraction in the United States

Abstract: SAC/VAL is associated with clinical benefit and may be cost-effective compared with the current standard of care over realistic treatment durations from the payer perspective. Results of this analysis can inform discussions on the value and position of SAC/VAL in the current market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“… 35 The cost-effectiveness of sacubitril versus valsartan in patients with systolic heart failure ranged from $45K to $144K in separate estimates. 36 , 37 Transcatheter aortic valve replacement had ICER estimates that ranged from $39 964 to $116 500 when compared with medical management; however, it was considered a disruptive therapy for a population with no other treatment options. 38 Transcatheter aortic valve replacement ICER estimates also ranged from $32 000 to $252 400 when compared with surgical valve replacement in patients with high risk of surgical mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 35 The cost-effectiveness of sacubitril versus valsartan in patients with systolic heart failure ranged from $45K to $144K in separate estimates. 36 , 37 Transcatheter aortic valve replacement had ICER estimates that ranged from $39 964 to $116 500 when compared with medical management; however, it was considered a disruptive therapy for a population with no other treatment options. 38 Transcatheter aortic valve replacement ICER estimates also ranged from $32 000 to $252 400 when compared with surgical valve replacement in patients with high risk of surgical mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, cardiac resynchronization therapy and implantable cardioverter defibrillators were generally cost-effective with ICERs ranging from $20,000 to $90,000/QALY gained. The findings of this study indicated the need for new pricing strategies to improve the cost-effectiveness of SAC/VAL [25].…”
Section: Cost Effectiveness Of Sacubitril/valsartanmentioning
confidence: 82%
“…But, a higher drug acquisition cost of SAC/VAL compared to traditional therapies had made its clinical utility questionable. The cost-effectiveness of SAC/VAL is influenced by all-cause mortality benefit, SAC/VAL drug costs, probability of NYHA class progression, and assumed duration of treatment (i.e., model time horizon) [25].…”
Section: Cost Effectiveness Of Sacubitril/valsartanmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently heart failure is the most expensive diagnostic‐related group for Medicare, because cost‐effectiveness of many of the recommendation for treatment is at best controversial. For example cost effectiveness ratio of ICD for primary prevention was below $ 100 000 only when effectiveness of ICD continued for at least 7 years and replacing ACE‐I by ARNI appears to be resulting in incremental cos‐effectiveness ratio of $ 143 891/QALY gained …”
Section: Effect Of Gdmt On Morbidity Compression In Heart Failurementioning
confidence: 99%